2019
DOI: 10.18203/2320-1770.ijrcog20196041
|View full text |Cite
|
Sign up to set email alerts
|

A study on feto-maternal outcome of intra hepatic cholestasis of pregnancy

Abstract: Background: Intrahepatic cholestasis of pregnancy is one kind of the hepatic disorder which is unique to pregnancy. It is associated with many adverse pregnancy outcomes if doesn’t intervened at right time. It requires adequate clinico-biochemical correlation during management.Methods: A prospective observational study was conducted at multispecialty government zonal hospital. Total 137 IHCP patients were managed during the study period from 01 Jan 2017 to 30 Jun 2019. Incidence and pregnancy outcome in form o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…16 A study conducted in India by Binay et al reported that first symptoms of cholestasis appeared in 34-36 weeks of pregnancy in 66% cases and in 32-34 weeks in 15%, before 32 weeks I n 14% while at 37 weeks in 5% cases. 17 Another similar study by Eshadi et al reported vaginal delivery in 56.7% and cesarean section in 43.3% cases. 18 Aftab et al found perinatal outcomes in their study as 29% cases had meconium stained liquor, abnormal CTG detected in 17%, 18% had intrauterine retarded growth, 26% were premature births while 3% had intrauterine fetal death.…”
Section: Discussionmentioning
confidence: 80%
“…16 A study conducted in India by Binay et al reported that first symptoms of cholestasis appeared in 34-36 weeks of pregnancy in 66% cases and in 32-34 weeks in 15%, before 32 weeks I n 14% while at 37 weeks in 5% cases. 17 Another similar study by Eshadi et al reported vaginal delivery in 56.7% and cesarean section in 43.3% cases. 18 Aftab et al found perinatal outcomes in their study as 29% cases had meconium stained liquor, abnormal CTG detected in 17%, 18% had intrauterine retarded growth, 26% were premature births while 3% had intrauterine fetal death.…”
Section: Discussionmentioning
confidence: 80%
“…Mitra B et al 2020 10 Gupta S et al 2022 19 Arthuis C et al 2022 22 Alsulyman et al 1996 25 Jhirwal M et al 2022 13 Our study MSL 29.93% Hablani K et al 2022 16 Gupta S et al 2022 19 Alsulyman et al 1996 25 Mitra…”
Section: Fetomaternal Outcomementioning
confidence: 80%
“…7 Fetal complications of IHCP likely to raised fetal serum bile acids taurocholic and taurodeoxycholic acid. 8 Alkaline phosphate (ALP) is raised normally in pregnancy and is considered abnormally high if there is at least 3 fold increase over the normotensive pregnant normal value (upper limit of normal range). All participants were closely monitored on a weekly basis by a clinical staff in an outpatient setting.…”
Section: Exclusion Criteriamentioning
confidence: 99%